2014
DOI: 10.1210/jc.2013-3274
|View full text |Cite
|
Sign up to set email alerts
|

Sitosterolemia Presenting With Severe Hypercholesterolemia and Intertriginous Xanthomas in a Breastfed Infant: Case Report and Brief Review

Abstract: Our case suggests that sitosterolemia can present with severe hypercholesterolemia and intertriginous xanthomas. Sitosterolemia should be suspected when a patient with hypercholesterolemia shows unexpectedly good response to dietary modification or bile acid sequestrant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 28 publications
4
47
1
1
Order By: Relevance
“…Park et al also reported a similar case to ours, in which a 15-month-old girl whose severe hypercholesterolaemia (serum LDL-C level, 540 mg/dl) was also complicated by intertriginous xanthomas during breastfeeding; her hypercholesterolaemia disappeared two months after the introduction of a low-fat/low-cholesterol diet and cholestyramine. She was diagnosed with compound heterozygous sitosterolaemia due to an ABCG5 gene mutation (Park et al 2014). Our findings of greatly reduced serum cholesterol levels seen after weaning in four infantile sitosterolaemic cases reinforce the previous findings (Table 1).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Park et al also reported a similar case to ours, in which a 15-month-old girl whose severe hypercholesterolaemia (serum LDL-C level, 540 mg/dl) was also complicated by intertriginous xanthomas during breastfeeding; her hypercholesterolaemia disappeared two months after the introduction of a low-fat/low-cholesterol diet and cholestyramine. She was diagnosed with compound heterozygous sitosterolaemia due to an ABCG5 gene mutation (Park et al 2014). Our findings of greatly reduced serum cholesterol levels seen after weaning in four infantile sitosterolaemic cases reinforce the previous findings (Table 1).…”
Section: Discussionsupporting
confidence: 90%
“…Although several papers have suggested the association between sitosterolaemia and haematologic abnormalities, such as macrothrombocytopaenia, haemolytic anaemia and splenomegaly (Park et al 2014;Wang et al 2014), none of our cases exhibited any abnormal haematological manifestations.…”
Section: Resultscontrasting
confidence: 80%
See 2 more Smart Citations
“…10,11 The condition should be considered even when consumption of plant sterols has not commenced, as phytosterols can be found in breast milk. 12 …”
Section: Clinical Sensitivity (Proportion Of Positive Tests If the DImentioning
confidence: 99%